33rd Zagreb Salon 1998. - Barak, Ami; Crtalic, Marijan; Devic, Ana; Molnar, Marijan; Perica, Blazenka; Rascic, Lala; Salomon, Sabina; Viculin, Marina; Vuksic, Helena Klakocar; Zabel, Igor; Zanki, Josip (Zagreb : MGC Klovicevi Dvori, 1998)
Martek, Vlado ; Martinis, Dalibor ; Vorih, Nenad ; Plejic, Toma ; Berc, Dafne ; Hrabak, Hrvoje ; Autora, Grupa ; Leko-Fritz, Kristina ; Horvat, Ana ; Vucemilovic, Fedor ; Rascic, Lala ; Fontana-Dujmic, Kristina ; Vukelic, Leo ; Tolj, Slaven ; Savic-Gecan, Tomo ; Kozaric, Ivan ; Jurjevic, Bozidar ; Jelavic, Ivana ; Badurina, Lara ; Simrak, Robert ; Demur, Boris ; Dolic, Jadranka ; Denic, Zrinka ; Crtalic, Marijan ; Roncevic, Igor ; Krasic, Ines ; Gotovac, Tomislav ; Zanki, Josip ; Dodig-Trokut, Vladimir ; Mlinar, Jadranka ; Delimar, Vlasta ; Fritz, Darko ; Vuk, Sonja ; Ivekovic, Sanja ; Poljak, Renata ; Molnar, Marijan ; Peristil, Crni ; Keser, Ivana ; Stilinovic, Mladen ; Kuduz, Igor ; Kocica, Ivona ; Babic, Kristina ; Narath, Simon B. ; Dukic, Sandro ; Ilic, Aleksandar ; Pino, I.J. ; Pavelic, Zoran ; Trbuljak, Goran ; Vodopija, Mirjana ; Sokic, Damir ; Gverovic, Tina ; Cinotti, Nini ; Kipke, Zeljko ; Vuksic, Helena Klakocar ; Mestrovic, Toni ; Jerman, Zeljko ; Petercol, Goran ; Kozul, Kristian ; Faktor, Ivan ; Cvjetanovic, Boris
33rd Zagreb Salon 1998, MGC Klovicevi Dvori, Zagreb, 15th May - 14th June 1998
Kroatisch & Engels
kunstcatalogus